Famasulö: Tradisi, Solidaritas, dan Kemiskinan Keluarga di Nias - Suciyadi Ramdhani; Risladiba Risladiba (Umbara, 2022)
This study aims to describe famasulö tradition at Nias and how it relates to family poverty. Famasulö is a tradition among Nias people to borrow money from kinship members in order to fund a wedding party. The study took place at Sirombu, West Nias. Ethnographic method was applied in the study; and the data were collected through in-depth interviews, observation, and literature review. The study found that Famasulö has been practiced since before people at Nias use banknotes as currency. Nias people view  wedding party as important ritual, and they attempt to hold it eventhough they are not yet financially capable. In fact, famasulö is a tradition that represents and strengthen family and kinship solidarity. However, it is often bring the families who practice it, into poverty. Eight families in this study have to face poverty and food scarcity because their income have been allocated to pay off debt due to famasulö. Thus, although the tradition can strengthen kinship solidarity,it is at the same time put families who practice, vulnerable to poverty.